A contradição entre a importância e o uso do google earth como recurso didático - Strey, Fábio (2014)
The main objective of this research is to search for answers, trough the use of Google Earth images, to teach the subject of Geography in Paraná's public schools, utilizing for sampling the schools belonging to the Regional Education Nucleus of Francisco Beltrão. As well as reflect about the teaching of Geography looking into the didactic-pedagogical process in the domain of categories and geotechnological information techniques in some aspects of the pedagogical relations, especially the reading of spatial representations. We seek to understand how teachers utilize Google Earth as a teaching resource in their classes. The justification for this theme lies on the value of cartographic visualization obtained from the images to the process of teaching and learning. The importance of this resource has been acknowledged by teachers. There is a contradiction, however, as all recognize the value of utilizing Google Earth but many do not actually utilize it. This can be explained by the impossibility of working Google Earth on the school, due to the lack o technology do to so. Still the merits of utilizing this resource in teaching Geography prevail, as was proved by the investigation and evaluation of the activities developed by the first year students of the Geography course of the State University of West Paraná, Francisco Beltrão campus.